Moderation Of Firm Size On The Effect Of Financial Performance On Tax Avoidance - Wirianata, Henny; Viriany; Tan Hauw-Sen (Jurnal Akuntansi, 2024)
This research was conducted to determine the influence of profitability, leverage, capital intensity, CSR, and firm size on tax avoidance and how firm size moderates this influence. The data in the research was taken using purposive random sampling by determining criteria from companies in the energy, basic materials, industrial, primary and secondary consumer goods sectors listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021. The data were processed and analysed using multiple regression and moderated regression analysis using Eviews 10. The research results show that profitability has a positive and significant influence on tax avoidance, and leverage has a negative and significant influence on tax avoidance. Capital intensity, CSR activities and firm size do not influence tax avoidance. The research results also show that firm size can moderate the influence of leverage and capital intensity on tax avoidance.